Territorial mechanisms and scaling processes for climate-smart agriculture in Guatemala - Borrayo, Andrea; Lizarazo, Miguel; Martinez, Deissy; Garcia, Jorge Octavio; Diaz, Anabell; Jimenez, Benancio; van Loon, Jelle; Carranza, Carlos; Hidalgo, Lisandro; García, Marcelo (2025)
Guatemala’s agricultural sector faces persistent challenges linked to climate variability, soil degradation, and the high vulnerability of smallholder production systems, particularly in hillside areas and the Dry Corridor. In this context, climate-smart agriculture has emerged as a key approach to strengthen resilience, stabilize productivity, and improve food security. However, its sustained adoption depends largely on the presence of territorial mechanisms that connect actors, infrastructure, and information to support informed and context-specific decision-making processes. This document systematizes and reorganizes evidence generated in Guatemala between 2023 and 2025 under the AgriLAC Resiliente initiative and the CGIAR Scaling for Impact (S4I) Science Program, with a focus on strengthening regional and local mechanisms and identifying entry points for scaling climate-smart agriculture. The analysis integrates evidence from innovation networks, territorial infrastructure, Local Technical Agroclimatic Committees (LTACs), agroclimatic bulletins, participatory research processes, and agronomic research platforms.